KARAKTERISASI BAJA KARBON ST 37 AKIBAT PACK CARBURIZING ARANG CANGKANG KEMIRI DENGAN KATALISATOR SERBUK KERANG ALE-ALE PANTAI OESAPA KOTA KUPANG - Wiskarjo, Marianus; Bunganaen, Wenseslaus; Jasron, Jahirwan Ut (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
This study aims to determine the changes in microstructure and the increase in hardness of low-carbon steel (ST 37) through the pack carburizing process. The method used involves utilizing charcoal derived from candlenut shells as a carbon source and ale-ale shell powder as a catalyst. The experiment was conducted using 10 steel specimens, where 9 specimens underwent pack carburizing treatment with variations in catalyst composition (10%, 20%, and 30% CaCO₃) at a temperature of 900°C with a holding time of 2 hours, followed by a quenching process using 40% saltwater. The results of the study indicate that the pack carburizing treatment successfully increased the surface hardness of the steel significantly and caused a microstructural transformation from ferrite-pearlite in the initial material to martensitic structure on the carburized surface. These findings suggest the potential use of natural materials as an environmentally friendly alternative for carbon media and catalysts to enhance the mechanical properties of low-carbon steel.